Leveraging technology in leadership communication - Kim, Carolyn Mae (New York, NY : Routledge, 2022)
"This book examines the intersection of leadership communication and digital technology, looking at how digital media can elevate or diminish a leader's influence. Using media ecology, this book explores the transitions in technology over the course of human history that resulted in today's digital communication environment. It builds on this understanding to examine the value leadership communication provides to engage employees and drive organizational objectives internally. Beyond examining internal or team communication, it also highlights the value of external stakeholder communication by leaders using tools such as social media or websites to elevate credibility. These chapters provide a framework to guide a leader's selection of digital tools and the application of those tools on communication with stakeholders. It examines various challenges to give a realistic assessment of how leaders can navigate digital communication successfully to thrive personally and professionally. Lastly, the book explores an often-missed dimension to leadership communication: followers. Using the ethicality of leadership and the role of followers, it concludes by examining guiding values for leadership communication in the digital age as well as forecasting future trends that will shape leader communication. The book is intended as supplementary reading in organizational, leadership, corporate, and internal communication undergraduate and graduate courses. Online instructor resources for this book include a one-sheet overview of how to use the text in a course as well as sample assignments and discussion questions"--
Includes bibliographical references and index.
Keywords: Communication in management; Leadership; Digital communications